Reframing Penal Policy: A Victim-Oriented Approach to Terrorism Victims in Indonesia: Mereformulasi Kebijakan Pidana: Pendekatan yang Berorientasi pada Korban bagi Para Korban Terorisme di Indonesia - Mutmainah Nur Qoiri; La Ode Muhammad Ichsan; Fathurozi Fathurozi; Shealsy Ainunna Mei Pratiwi; Wei-Cheng Lin (Indonesian Journal of Counter Terrorism and National Security, 2026)
The protection of victims of terrorism is an integral part of a just criminal law system. The state has the obligation not only to punish the perpetrators, but also to restore the condition of the victims through effective legal means. However, regulations governing victims’ rights in Indonesia’s criminal justice system, despite normative strengthening through Law Number 5 of 2018 and Government Regulation in Lieu of Law (Perppu) Number 1 of 2002, have not yet shown full compliance with victim-oriented principles. Research that examines the rights of victims of terrorism by analyzing the victim-oriented framework is still limited. This research aims to evaluate Indonesia’s criminal law policy in order to further improve the protection of victims of terrorism by using a victim-oriented approach. The method used is normative juridical by searching legal documents and relevant international references, including documents and policies that develop the principles of victim protection in the criminal justice system. The results showed that although there is recognition of victims’ rights, such as compensation, restitution, medical assistance, psychosocial and psychological rehabilitation, there are still other victims’ rights that must be fulfilled, such as protection for victims of vulnerable groups and the involvement of victims in the criminal justice system. The implication of this finding is the need for policy reformulation that makes victim orientation to make victims subjects who must be healed and engaged.